Impact of neuroendocrine morphology on cancer outcomes and stage at diagnosis: A UK nationwide cohort study 2013–2015 - Genus, TSE; Bouvier, C; Wong, KF; Srirajaskanthan, R; Rous, BA; Talbot, DC; Valle, JW; Khan, M; Pearce, N; Elshafie, M; Reed, NS; Morgan, E; et al. (Springer Nature, 2019)
Background: The diagnosis of neuroendocrine neoplasms (NENs) is often delayed. This first UK population-based epidemiological study of NENs compares outcomes with non-NENs to identify any inequalities.